Plenitude of mathematics in architecture and its infinite possibilities: a review of parametric design - Nur Amalina Hanapi; Jakathisvaran; Syafa Sakinah Mustaffa; Hanna, Raid (Penerbit Universiti Kebangsaan Malaysia, 2022)
During the earlier stage of architectural education, we are exposed to the concept of mathematics in architecture such as the Vitruvian man, the golden ratio, the Cartesian, Euclidean and Pythagoras Theorem. After a while this so-called basic architectural knowledge is no longer that matter that we are much consumed by the freedom of art and aesthetic that drove us to oversight that science and technology are also important parts of architecture that we should never overlook. Therefore, this paper explores the use of mathematics in architecture, and how it can contribute in revolutionizing the architecture to a different and logical spectrum. Case studies, site visits and observations are conducted on selected buildings that used applied mathematics in the design process such as British Museum, England (parametric design), Sydney Opera House, Australia (algo rithm design), and Segrada Familia , Spain (sequence number). The paper suggests that it is been retained in a new emerging style of parametricism as the only way for the ideology survive with a better understanding of mathematics as an underlying principle and reasoning.